2019
DOI: 10.12968/bjom.2019.27.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal expectations of antenatal education across the transition to parenthood

Abstract: This study uses research evaluation data to explore parents' expectations from antenatal classes as they transition from pregnancy to the post-natal period. Understanding parents' expectations over this time with respect to knowledge and skills provides an opportunity to tailor antenatal classes more closely to the needs of parents. Equally, it is important to understand, if, and how, these expectations are met during the transition to parenthood. Understanding parents expectations of antenatal classes, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…They also confirm that health care during pregnancy should include the pregnant couple, which is also a recommendation of other studies (Entsieh & Hallström, 2016;Palsson et al, 2017). Contrary to Jones et al (2019), no significant differences were observed between mothers' and fathers' needs. Therefore, based on the results, it can be said that mothers and fathers have overlapping needs.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…They also confirm that health care during pregnancy should include the pregnant couple, which is also a recommendation of other studies (Entsieh & Hallström, 2016;Palsson et al, 2017). Contrary to Jones et al (2019), no significant differences were observed between mothers' and fathers' needs. Therefore, based on the results, it can be said that mothers and fathers have overlapping needs.…”
Section: Discussionsupporting
confidence: 81%
“…These prenatal care interventions designed and implemented by nurses, namely by specialist nurses in MOHN, are key to saving lives, improving well-being and healthcare utilization, and increasing the quality of care. Today, the transition to parenthood is a desired experience by most couples, and, for this reason, even during pregnancy, they are highly engaged in the adoption of healthy behaviors and early preparation for the next stage (Cardoso, 2011;Jones et al, 2019). This predisposition for active participation is visible in women, but a growing interest has also been observed among men (Andersson et al, 2016), particularly regarding preparation for parenthood (Entsieh & Hallström, 2016;Mniszak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Television and Internet were also identified as preferred sources of information [6]. Moreover, [26] reported that exploring the value of ante natal classes among pregnant women has the potential to result to improve attendance, reduced dropout rates and overall greater satisfaction. Reference [8] documented that antenatal education can be provided in a rural community using drama, reading picture Both content and methods of antenatal education have changed over time without evidence of effects on relevant outcomes.…”
Section: Introductionmentioning
confidence: 99%